Predictive factors of anastomotic leakage in laparoscopic colorectal surgery - Castor Siqueira Freire Viana, Verônica Rafaela; Carballo, Federico Héctor Enrique (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Background: Anastomotic leakage represent one of the most alarming complications after any gastrointestinal anastomosis. According to the predictive factors analyzed, the postoperative morbidity and mortality suffered by patients are long-lasting consequences on functional and oncological results. Its incidence is 3%-6%, even in experienced hands. There is a lack of consensus regarding its definition, with a variety of options for prevention and treatment. Various risk factors have been found to be associated with the development of an anastomotic dehiscence and have inspired the development of various preventive measures and technologies. AIM: determine the most relevant predictors of anastomotic dehiscence available in the current literature. Material and methods: For the development of the research protocol, the PRISMA statement has been followed by systematically, observationally, analytically, and retrospectively reviewing the literature. Articles and studies that address the risk factors for AL during laparoscopic colorectal surgery have been selected, as well as all the current knowledge on its management and post-surgical repair. A bibliographic search was carried out in electronic databases (PubMed, MEDLInE, EMBASE). Results: 16 articles were selected that coincided in their analyzes describing the following risk factors: smoking, advanced age, surgical technique and material used, prolonged operating time and late diagnosis. They are configured as a risk for the occurrence of anastomotic dehiscence, in addition to also recognizing the negative conditions that derive from this complication, such as increased hospitalization time, hospital expenses, and increased morbidity and mortality rates due to AD. Conclusion: prevention is the best way to avoid anastomotic leakage as a post-surgical complication, for this we must highlight the importance of analyzing the risk factors of each patient individually at an early stage such as male sex, a low anastomosis, a BMI greater than 30 and others. In order to adapt a personalized therapeutic plan and thereby reduce morbidity and mortality rates